EFL Students’ Self-Directed Learning of Listening Comprehension Skill using YouTube Videos (Jurnal Sosial Humaniora dan Pendidikan, 2026)
English has developed into a global language that is widely spoken and used as a second language in a number of countries. As a result, people recognize the importance of English fluency in all aspects of global communication. Technology advances at a breakneck pace in the twenty-first century. YouTube is Indonesia's second most popular social media platform. With YouTube's popularity, it has the potential to become a TELL product as a learning medium. Listening is a critical talent that everyone should acquire and practice. Listening is the process through which listeners process information obtained from visual and aural cues in order to identify what is happening and what the speakers are attempting to express (Rubin, 1995). This study investigated the impact of using YouTube on the listening skills of adult students of English as a foreign language in Bekasi, Indonesia. The findings of this study are based on observations of EFL students who are taught listening skills through the use of audio recordings and demonstrate a low level of motivation to learn. This study also looked into how YouTube can help EFL students become more motivated.